Analyzing the meteorological parameters in the vicinity of slaughterhouses - Maduforoh, Collins (Faculty of Natural and Applied Sciences Journal of Applied and Physical Sciences, 2024)
This study investigates the influence of meteorological factors on pollutant concentrations around slaughterhouses in Port Harcourt, Nigeria. The aim is to assess how temperature, relative humidity, and wind speed affect air quality in these industrial areas. A descriptive research design was employed, and data on meteorological parameters were collected at five slaughterhouse sites during morning and evening periods over twelve months. The results reveal significant variations in meteorological parameters across slaughterhouses, with Eleme consistently exhibiting higher relative humidity and temperature values. These values often exceeded the standards set by the World Health Organization, indicating potential health risks due to poor air quality. Wind speed, crucial for pollutant dispersion, also varied significantly among locations. The interconnectedness of these factors underscores their complex influence on pollutant concentrations. Elevated temperatures, likely influenced by prevailing winds and combustion activities, contributed to increased pollutant concentrations, while higher wind speeds facilitated faster dispersion. In conclusion, the study highlights the urgent need for stricter regulations and enforcement measures to control emissions from slaughterhouse activities. Enhanced air quality monitoring, public awareness campaigns, and collaborative efforts among stakeholders are recommended to mitigate the adverse effects of air pollution on public health and the environment. Further research is warranted to understand the long-term impacts of air pollution from slaughterhouses and devise targeted strategies for improving air quality in urban settings.